Assessment of redox state and biochemical parameters of salivary glands in streptozotocin-induced diabetic male rats treated with mate tea (Ilex paraguariensis) - Gomes, Marco Aurélio [UNESP]; Manzano, Carolina [UNESP]; Alves, Thayane Miranda [UNESP]; Fiais, Gabriela Alice [UNESP]; Freitas, Rayara Nogueira [UNESP]; Coutinho Mattera, Maria Sara de Lima [UNESP]; Dornelles, Rita Cássia Menegati [UNESP]; Matsushita, Doris Hissako [UNESP]; Stevanato Nakamune, Ana Cláudia de Melo [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP] (Elsevier, 2022)
Objective: The study aimed to assess the effects of mate tea [Ilex paraguariensis] on the redox state and biochemical parameters of salivary glands in diabetic male rats. Design: Twenty-four male Wistar rats (3 months old) were randomly divided into groups (n = 8 per group): control rats that received water (C); diabetic rats that received water (D); diabetic rats treated with mate tea (DMT). The treated streptozotocin-induced diabetic rats were given mate tea powder by intragastric gavage at a dose of 20 mg/kg daily for 28 days. Content of total protein, amylase, oxidative lipid damage, measured as thiobarbituric acid reactive substances (TBARs), oxidative protein damage, measured as protein carbonyl, total antioxidant capacity, uric acid, reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were examined by the spectrophotometric method in the parotid and submandibular glands. Results: The D group showed lower total protein, amylase, TBARs, protein carbonyl, total antioxidant capacity, GSH, uric acid, and GPx than the C group in both salivary glands, as well as higher SOD and CAT activities. The DMT group showed higher total protein, amylase, total antioxidant capacity, GSH, uric acid, and GPx than the D group in both salivary glands. Moreover, mate tea increased SOD in the parotid gland and CAT in the submandibular gland of diabetic rats but did not influence TBARs and protein carbonyl in either salivary gland compared to D group. Conclusion: Mate tea increased tissue protein synthesis and improved antioxidant defenses in the salivary glands of streptozotocin-induced diabetic male rats.
Keywords: Antioxidant; Diabetes Mellitus; Experimental; Ilex paraguariensis; Parotid gland; Submandibular gland